COMPARATIVE ANALYSIS OF THE INFLUENCE OF REGIONAL LEADING SECTORS AND NON-LEADING SECTORS ON ECONOMIC GROWTH BETWEEN CORE DISTRICT AND ITS EXPANSION AREA: (Case Study in West Aceh District and Its Expansion Area) - Yayuk Eko Wahyuningsih; T. Zulham; Leli Putri Ansari (Jurnal Ilmiah Teunuleh, 2021)
This study aims to analyze the potential of the regional superior sector in West Aceh Regency and its expansion area by using Location Quotient analysis or abbreviated as LQ towards a sustainable economy in the new normal era. The data used is secondary data sourced from the Central Statistics Agency for each district and province of Aceh. Gross regional domestic product data for the 2010-2020 period is 17 sectors. The results showed that the highest LQ value in Simeulue Regency was 2.18 for the government administration sector, then 1.51 for the agriculture, forestry and fishery sectors. For information, this district excels in lobster cultivation. Next is Nagan Raya Regency with an LQ of 2.88 in the mining/excavation sector and 1.52 in the agriculture/plantation sector. This value is obtained because this district excels in mining C and oil palm plantations. Then Aceh Jaya with an LQ of 1.81 in the construction sector and 1.55 in the transportation sector because this area is superior in terms of tourism. Finally, West Aceh Regency with an LQ value of 1.59 for the financial/information services sector. While in the agricultural/forestry sector it is 1.17 because this district excels in financial services and is the largest city on the southwest coast of Aceh. The leading sectors above must still be managed properly, especially local potentials while still paying attention to a sustainable environmental economy. This is not excessive considering that in this new normal era, the economy must continue to rise even in the midst of the COVID-19 pandemic by sticking to health protocols.